Trends in management of acute lymphoblastic leukemia: Influence of insurance based healthcare and treatment compliance on the outcome of adolescents and adults with acute lymphoblastic leukemia - Arigela, Ravi; Gundeti, Sadashivudu; Ganta, Ranga; Nasaka, Srividhya; Linga, Vijay; Maddali, Lakshmi (Indian Journal of Medical and Paediatric Oncology, 2016)
Aim: In this study, we attempted to analyze the impact of insurance based health care system and treatment compliance on the outcome of adolescent and adults with acute lymphoblastic leukemia (ALL). Materials and Methods: Patients who underwent treatment for ALL during the period 2003-2011 were enrolled into this retrospective study. Patients on supportive or palliative care only and patients with age <10 years were excluded. The hospital records and tumor registry records were studied. Patients were stratified into two groups, Group A (prior to the introduction of state health insurance [SHI], 2003-2007) and Group B (after the introduction of SHI, 2008-2011). Overall survival (OS) was calculated using Kaplan-Meier method. Results: A total of 420 patients with suspected or confirmed ALL visited our center during the study period and 179 patients (87 in Group A and 92 in Group B) were considered for inclusion. The median age in years (range) was 18 (10-57) and 18 (10-58) respectively in Groups A and B with males more than females. Median OS (95% CI) was 9 (6.7-11.2) and 12 (7.3-16.7) months in the Groups A and B respectively (P = 0.265). Poor treatment compliance in both groups was high (36% in Group A and 41% in Group B, [P = 0.107]) with lower default rates in Group B (P = 0.019). Patients with good compliance in the total study population and the individual study groups had significantly better OS. Conclusions: Insurance based health care has improved outcomes in the present study but not compliance to treatment. Significantly better OS was observed in patients with good compliance.
Keywords: Acute lymphoblastic leukemia; adult; compliance; health care; insurance